Highly stretchable and sensitive strain sensor based on liquid metal composite for wearable sign language communication device. (24th September 2021) - Zhang, Qingtian; Yun, Guolin; Zhao, Beiliang; Lu, Hongda; Zhang, Shiwu; Tang, Shi-Yang; Li, Weihua
Abstract: In recent years, the demand for wearable strain sensors is growing due to their motion monitoring and clinical data collection capabilities. The sensors with positive piozeconductivity, i.e. their conductivity increases when stretched, are more favored in wearable electronics because they can maintain high conductivity under stretching. However, reported composites with positive piezoconductivity mostly show low sensitivity. Furthermore, few wearable electronic systems based on strain sensors are built completely with data processing capabilities. Herein, we present a wearable sensor based on a positive piezoconductive composite composed of liquid metal microdroplets, metal microparticles, and elastic matrix. The resistance of the composite is extremely high at the relaxed state but drops drastically under any deformation. It has high stretchability (fracture strain >200%) and sensitivity (gauge factor ∼100), which shows excellent performance in detecting human motions such as joint bending. Based on this composite, we demonstrate a wearable and portable sign language communication device with a fully programmable and configurable system to help people with language disabilities communicate effectively with others from the visual and auditory perspectives. By bending the fingers, the device can type words or sentences on screen and speak relevant letters through the audio.